GENDER FEATURES CYTOCHEMICAL ACTIVITY BLOOD MONOCYTES IN PATIENTS WITH CHRONIC VIRAL HEPATITIS WITH MODERATE ACTIVITY - A. A. Alieva (Кубанский научный медицинский вестник, 2014)
The aim of this work is to study changes in functional activity of blood monocytes in patients with chronic hepatitis C virus (HCV), depending on the dynamics of gender-specific treatment. Our studies have shown that monocytes of men with chronic hepatitis C before treatment of moderate activity observed voltage diaphorase and esterase activity, and LDH, with the oppression of LDH activity and G-6-PDG. In women, however, a sharp voltage spectrum of enzymatic test monocytes. The use of combined therapy (with the addition of cycloferon) in men caused a complete normalization of enzymatic spectrum (both quantitative and qualitative). Women have completely returned to normal activity esterase and diaphorases.